DIRECT PLANT REGENERATION FROM COTYLEDONARY EXPLANTS OF BLACKGRAM (VIGNA MUNGO L.) HEPPER. - THALLAPALLY SRILATHA, (International Journal of Pharma and Bio Sciences, 2014)
The present study was undertaken to investigate the possibility for developing Efficient Plant regeneration protocol in Vigno mungo L. For this, the effect of Cytokinens on in vitro regeneration from Cotyledonary explants was studied in Black gram (Vigno mungo L.) Hepper Var Vamban-1. The cytokinins used were 6-benzylaminopurine (BAP), Thidiazuron (TDZ), and kinetin (Kn). The regenerated shoots elongate on the same medium. TDZ stimulated shoot regeneration and this effect was significantly enhanced. (4.0 mg/L) was proved to be best for induction of shoots from cotyledon explants The regenerated shoots elongated 5 cm for four weeks on the same medium. Micro shoots were rooted on MS medium fortified with IBA (3.0mg/L) followed by transfer to green house. We conclude that TDZ induces significant regeneration as well as shoot elongation from cotyledon in Black gram ver Vamban-1. For the first time our findings describe a direct protocol for in vitro shoot regeneration and elongation in Black gram with cytokinins.